Peningkatan Kompetensi Guru melalui Pelatihan Keterampilan Pembuatan E-Presentation - Somantri, Oman; Abidin, Taufiq; Wijayanto, Sena; Wibowo, Dega Surono; Dairoh, Dairoh (Uhamka Press, 2019)
Electronic presentations are media presentations made using various tools such as powerpoint, prezy and others that are useful for presenting to audiences from various fields, be it business, offices or education. Pusponegoro Vocational School currently has difficulties in finding appropriate media in the current situation, which it wants to improve the pattern of the distribution system in the school, so in this case the electronic manufacturing presentation is using through training activities. The method of activity used to achieve the objectives of this community service activity is the lecture method and practice using powerpoint and Prezy media where all the training participants after getting the material presented then practice what has been given its implementation. Based on the results of community service activities, it can be concluded that the knowledge and understanding of the application of electronic presentations given to the Pusponegoro Jatibarang Vocational School Teachers who participated in the training can provide new insights into the use of alternative learning media that can be used in the learning process.